2021
DOI: 10.1111/mpp.13140
|View full text |Cite
|
Sign up to set email alerts
|

Novel factors contributing to fungal pathogenicity at early stages of Setosphaeria turcica infection

Abstract: Setosphaeria turcica is the causal agent of northern corn leaf blight, which is one of the most important maize foliar diseases (Cao et al., 2020;Perkins & Pedercens, 1987;Van Inghelandt et al., 2012). Early infection starts when a conidium of S. turcica lands on the maize leaf surface and germinates to form a highly polarized germ tube.The germ tube elongates and becomes flattened against the plant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…VmE02 is a cell death inducer isolated from V. mali and later identified as a novel transboundary PAMP with a wide distribution in oomycetes and fungi (Nie et al, 2019). A recent study has shown that StACE1 acts as an appressorium-coupled effector that can cause cell necrosis in N. benthamiana (Meng et al, 2022). There is, however, limited research on S. turcica effectors or PAMPs, which can trigger cell death and control host immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VmE02 is a cell death inducer isolated from V. mali and later identified as a novel transboundary PAMP with a wide distribution in oomycetes and fungi (Nie et al, 2019). A recent study has shown that StACE1 acts as an appressorium-coupled effector that can cause cell necrosis in N. benthamiana (Meng et al, 2022). There is, however, limited research on S. turcica effectors or PAMPs, which can trigger cell death and control host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Northern corn leaf blight (NCLB) is caused by Setosphaeria turcica and is one of the major foliar diseases in maize production areas worldwide (Jackson-Ziems, 2016;Meng et al, 2022). Yield losses usually range from 15 to 30%, up to 50% in severe cases (Raymundo and Hooker, 1981;Perkins, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous method, positive colonies were screened on CMD-W medium, and the utilization of ra nose by yeast was observed on YPRAA medium to verify the function of signal peptide (Liu, et al 2021b). The activity of sucrose transferase was detected using 2% TTC solution to verify the function of signal peptide (Meng, et al 2022).…”
Section: Yeast Signal Peptide Capture Testmentioning
confidence: 99%
“…Briefly, the infection occurs when a conidia spore germinates on a leaf, producing an appressorium and infection peg, and the infective hyphae enter the mesophyll (Chung et al., 2010b; Galiano‐Carneiro & Miedaner, 2017). Setosphaeria turcica employs cell wall degrading enzymes to penetrate into the leaf (Meng et al., 2021), invading the plant cell and cellular space. The growing mycelium grow toward the xylem in the vascular bundle, and vascular plugging ensues along with colonization of neighboring bundle sheath cells.…”
Section: Introductionmentioning
confidence: 99%